The lion above the door - Raúf, Onjali Q. 1981- (Orion, 2021)
"Leo and his best friend Sangeeta are the odd ones out in their school. But as Leo's dad is always telling him, it's because they're special. Only thing is, if they're so special, how come they never see anyone who looks like them in their school history books? Then, on a class trip to a nearby cathedral, Leo's attention is drawn to a large marble slab high above the doors of the hall. Right there, bang in the middle of a list of war heroes, Leo finds himself staring at something incredible: his own name. Desperate to know who this other Leo was, the two friends embark on a search. And together, they begin to uncover missing stories from the past, ones which they are determined to put back into their rightful place in the pages of history. Touching on themes of historical racism, The Lion Above the Door shines a light on the stories our history books have yet to contain and the power of friendships that can last through generations. The first edition of this book also contains a special collection of historical photos and stories of real life forgotten heroes from World War Two"--Publisher's description
The first edition of this book also contains a special collection of historical photos and stories of real life forgotten heroes from World War Two
Keywords: Rassismus; Identitätsfindung; Identität; Held; Zweiter Weltkrieg; Vorurteil; Junge; Best friends / Juvenile fiction; Families / Juvenile fiction; Schools / Juvenile fiction; World War, 1939-1945 / Juvenile fiction; Heroes / Juvenile fiction; Amis / Romans, nouvelles, etc. pour la jeunesse; Familles / Romans, nouvelles, etc. pour la jeunesse; Écoles / Romans, nouvelles, etc. pour la jeunesse; Guerre mondiale, 1939-1945 / Romans, nouvelles, etc. pour la jeunesse; Héros / Romans, nouvelles, etc. pour la jeunesse; Histoires pour enfants; JUVENILE FICTION / Social Themes / Prejudice & Racism; JUVENILE FICTION / Historical / Military & Wars; Kinderbuch